The influence of early life nutrition on adipose tissue development is modulated by age in sheep - Alhaddad, Ahmad (2019)
Introduction Non-shivering thermogenesis in brown adipose tissue (BAT), mediated by a unique uncoupling protein (UCP1), is essential for metabolic adaptation birth in large mammals such as sheep. BAT then undergoes substantial changes as UCP1 is gradually lost and replaced with white adipose tissue (WAT) which mainly acts as a fat storage tissue. Given BAT can be retained into later life a better understanding of this process could enable the maintenance of BAT function by modifying its transition to WAT in early life. Ultimately this could provide a potential target to prevent obesity in adulthood.